2017
DOI: 10.1155/2017/2185351
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow Mesenchymal Stem/Stromal Cells Preserve Their Immunomodulatory and Chemotactic Properties When Expanded in a Human Plasma Derived Xeno-Free Medium

Abstract: Due to their immunomodulatory and chemotactic properties, hMSC are being explored to treat immune-related diseases. For their use in human therapies, it is necessary to culture hMSC in xeno-free conditions. In this study, the impact that a xeno-free medium based on a human plasma derivate has on these properties was analysed. Bone marrow-derived hMSC preserved their immunosuppressive and immunostimulatory properties, as observed with in vitro assays with hMSC cocultured with mixed leukocyte reactions or with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Isolation and expansion techniques are still not standardized harboring the risk of variable quality of MSC cell preparations. Currently, MSC differentiation during expansion and related loss of function cannot be monitored by quality control assays, but expansion in cell culture using xeno-free media represents a promising research direction [ 147 ]. Furthermore, expansion of autologous MSCs should be taken into the conceptual consideration to overcome the risks and ethical concerns of allogenic transplantation.…”
Section: Current Therapeutic Obstacles To Msc Therapymentioning
confidence: 99%
“…Isolation and expansion techniques are still not standardized harboring the risk of variable quality of MSC cell preparations. Currently, MSC differentiation during expansion and related loss of function cannot be monitored by quality control assays, but expansion in cell culture using xeno-free media represents a promising research direction [ 147 ]. Furthermore, expansion of autologous MSCs should be taken into the conceptual consideration to overcome the risks and ethical concerns of allogenic transplantation.…”
Section: Current Therapeutic Obstacles To Msc Therapymentioning
confidence: 99%
“…Still, allotransplantation risks are present, although phase I clinical trials do not show any short-term side effects [ 57 , 66 , 67 ]. Presently, the differentiation of MSCs and the loss of related functions cannot be monitored by quality control experiments [ 68 ]. Most recently, GMP-grade MSCs derived from hiPSCs have been used in refractory graft-versus-host-disease (GVHD) in clinical trials [ 69 ].…”
Section: Current Challenges In Msc Treatmentmentioning
confidence: 99%
“…MSC transplantation for BPD treatment requires ethical review and evaluation before clinical trials. The differentiation and related functional loss of MSCs during amplification cannot be monitored by quality control analysis, but cell culture without animal components is a promising research direction [ 68 ]. Moreover, conceptually, the expansion of MSCs should be considered to overcome the risks and ethical concerns of allotransplantation.…”
Section: Current Challenges In Msc Treatmentmentioning
confidence: 99%
“…Moreover, it has been suggested that these supplements are suitable for in vitro expansion of MSCs (Haque and Abu Kasim 2017;Bieback et al 2012;Blazquez-Prunera et al 2017b). Several recent studies suggested that the immunomodulatory properties of MSCs are dependent on the type of supplements such as FBS, pHS and commercially produced cell culture supplement that used for their expansion (Blazquez-Prunera et al 2017a;Komoda et al 2010). However, no major complications have been reported in clinical trials using MSCs expanded with different supplements (Yubo et al 2017;Yim et al 2016).…”
Section: Introductionmentioning
confidence: 99%